EFFECT OF L-929 DERIVED SECRETOME ON HUH-7 HEPATIC CANCER CELL- ON CELLULAR PROLIFERATION AND OXIDATIVE STRESS - Singh, Virbhan; Sharma, Mridul; Rai, Seemha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The tumor microenvironment (TME) plays a crucial role in cancer progression, where stromal components such as fibroblasts actively influence tumor cell behavior. This study investigates the effects of the secretome derived from L-929 fibroblasts on HuH-7 hepatic cancer cells on cellular proliferation and oxidative stress. The interaction between fibroblast-derived factors and hepatic carcinoma cells has not been extensively explored. Through in vitro assays, including MTT and ROS analysis, it was found that L-929 fibroblast secretome decreased the HuH-7 proliferation and also induced oxidative stress in HUH-7 cells. The findings contribute to a deeper understanding of tumor-stromal interactions and potential therapeutic implications for hepatocellular carcinoma (HCC).